Lactobacillus probiotics for treating functional dyspepsia in children - Tuty Ahyani; Supriatmo Supriatmo; Melda Deliana; Ade Rachmat Yudiyanto; Atan Baas Sinuhaji (Indonesian Pediatric Society, 2016)
Background Functional dyspepsia is a common gastrointestinal disorder in school-aged children, though, there is no reliable treatment. Probiotics are live microorganisms administered in adequate amounts to confer beneficial health effects on the host. Although definitive evidence is lacking, several studies have found probiotics to be effective for relieving symptoms of dyspepsia, particularly abdominal pain and bloating.Objective To determine the efficacy of lactobacillus probiotics for treating functional dyspepsia in children.Method A double-blind, randomized controlled trial was done from April to June 2012 in five schools in the Pakpak Bharat Regency, North Sumatera. A total of 116 children who fulfilled the Rome III criteria for functional dyspepsia were randomized into 2 groups to receive either lactobacillus probiotics or placebo for 2 weeks. All patients received a diary to record symptoms and frequency of pain daily. The primary outcome for treatment was defined to be no pain at the end of the intervention.Results The probiotics and placebo groups were not significantly different in recovery from functional dyspepsia (29.3% vs. 13.8%, respectively; P=0.432). However, compared to the placebo group, the probiotics group had significantly reduced frequency of pain (P=0.0001), but no significant differences in pain severity (P=0.08) or pain duration (P 0.091).Conclusion There are no significant differences in recovery from functional dyspepsia, pain severity, or pain duration between the probiotics and placebo groups. However, the probiotics group has significantly reduced frequency of pain compared to that of the placebo group.